Synthesis of Nanoparticulate PrFeO3 by Sol–Gel Method and its Visible-Light Photocatalytic Activity. (4th July 2019) - Tang, Peisong; Xie, Xinyu; Chen, Haifeng; Lv, Chunyan; Ding, Yangbin
Abstract: Perovskite rare-earth ferrate PrFeO3 is a new kind of photocatalytic material. Using Fe(NO3 )3 ·9H2 O, Pr(NO3 )3 ·6H2 O, citric acid and urea as main raw materials, the gel of PrFeO3 was prepared by sol–gel method. The gel was kept at 80 °C for 48 h to make xerogel. Then, the xerogel was calcined in muffle furnace at 800 °C to obtain PrFeO3 samples. The structure and morphology of samples were characterized by thermogravimetry and differential scanning calorimetry (TG-DSC), powder X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR) spectroscopy and UV–visible diffuse reflectance spectroscopy (DRS). The results showed that the perovskite structure PrFeO3 was obtained through sol–gel method. The resulting products have a particle size of 80 nm and an optical band gap of 2.4 eV. Consequently, the PrFeO3 nanoparticles showed high photocatalytic activities for decomposition of methyl orange under visible-light irradiation. The PrFeO3 samples are consistent with first-order kinetics for the degradation of methyl orange. And the apparent rate constants is k = 0.071 min −1 .